Case Report: Nintedaninb May Accelerate Lung Recovery in Critical Coronavirus Disease 2019 - Bussolari, Cecilia; Palumbo, Diego; Fominsky, Evgeni; Nardelli, Pasquale; De Lorenzo, Rebecca; Vitali, Giordano; De Cobelli, Francesco; Rovere-Querini, Patrizia; Scandroglio, Anna Mara (Frontiers in Medicine, 2021)
Severe Coronavirus disease 2019 (COVID-19) is characterized by acute respiratory distress syndrome (ARDS) which may lead to long-lasting pulmonary sequelae in survivors. COVID-19 shares common molecular signatures with interstitial lung diseases (ILDs), including pro-angiogenic and tissue remodeling mechanisms mediated by vascular endothelial growth factor receptor (VEGF-R), fibroblast growth factor receptor (FGF-R) and platelet-derived growth factor receptor (PDGF-R). Nintedanib mainly targets these factors and is approved for ILDs. Therefore, we administered nintedanib through compassionate use to three patients with COVID-19 pneumonia requiring extra-corporeal membrane-oxygenation (ECMO). Here, we describe our experience in an attempt to explore the role of nintedanib in lung recovery in COVID-19. Three obese patients aged between 42 and 52 years were started on nintedanib due to difficulty obtaining lung function restoration and weaning from ECMO support following removal of orotracheal intubation. Soon after treatment start, systemic inflammation and respiratory function rapidly improved and ECMO support was withdrawn. Serial chest computed tomography scans confirmed the progressive lung amelioration, also reflected by functional tests during follow-up. Nintedanib was well-tolerated by all three patients at the dosage used for ILDs and continued for two-three months based on drug availability. Although caution in interpreting events is required, it is tempting to speculate that nintedanib may have contributed to modulate lung inflammation and remodeling and sustain lung repair. Altogether, nintedanib appears as a promising agent in patients with severe COVID-19 and delayed respiratory function recovery, for whom molecularly targeted therapies are still lacking. Clinical trials are necessary to confirm our observations.